Effect of two rootstocks on growth, yield and nut characteristics of ‘Mateur’ and ‘Achouri’ pistachio varieties - Ouni S.; Chelli-Chaabouni A.; Ouerghi I.; Ben Hamda H.; Rhouma A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
This experiment aimed to study the effect of rootstock on 25-year-old pistachio trees in the Tunisian northeast rainfed conditions. ‘Mateur’ and ‘Achouri’ female varieties were grafted onto Pistacia vera and Pistacia atlantica rootstocks. The vegetative and flower bud breaks have been followed from April to June. The diameter growth of current year shoot was measured. The architecture of flower clusters was studied. Yield and fruit weight, size and dehiscence rate were determined. Results showed no effect of rootstocks on the date of vegetative bud break for both cultivars. ‘Achouri’ developed flower clusters earlier on P. atlantica rootstock and showed a significantly higher shoot diameter growth on P. vera rootstock. The nut size characteristics showed no significant differences between both combinations cultivar/rootstock for ‘Mateur’. These parameters were significantly higher on P. atlantica rootstock for ‘Achouri’. According to these preliminary results, rootstock seemed not to affect growth and nut quality of ‘Mateur’ cultivar while P. atlantica rootstock appeared to have some beneficial effects on ‘Achouri’.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)